Exploring the characteristics of spatial distribution for Sperm whales (Physeter macrocephalus) and Northern bottlenose whales (Hyperoodon ampullatus) in the Arctic : a preliminary study to inform conservation management - Davidson, Ellyn, 1988- (2016)
Verkefnið er unnið við Háskólasetur Vestfjarða Very little is known about how sperm whales and northern bottlenose whales use their Arctic habitat. A long time series of presence data from two datasets was used to map the sighting density and spatial distribution of both species within Baffin Bay and Davis Strait. A taxon-based approach was used and pseudo-absence values were assigned to non-focal species that were also recorded within the datasets. The results indicated high sperm whale sighting density on the east side of the study site near Nuuk, and sparse sighting density on the southwest side and central west side of the study site. Data on sea surface temperature, sea surface salinity, depth and slope were incorporated into the study and relationships between these variables and whale sightings were explored through the creation of generalized additive models. The best-fit models were chosen from all available model combinations based on the lowest AIC values. The results indicated a relationship between the sperm whales sighted on the east side and all variables, between the sperm whales sighted on the west side and sea surface salinity, and between the northern bottlenose whales sighted on the west side and depth and slope. However, these results were specific to the variables included in the models and could differ if more predictive variables (i.e. prey distribution or proximity to frontal zones) are included in the future. Furthermore, the model results and the sighting density patterns could not be generalized for absolute species distribution as data was only available for summer and early autumn and other variables (i.e. sea ice) could impact distribution patterns in different seasons. The results suggest a northward range expansion for sperm whales from areas previously reported. The results also recommend the investigation of the central west region as an area of importance to northern bottlenose whales. This project calls for the increase of data collected for both of these species in the ...